Mapping Research Trends on Learning Trajectory in Mathematics Education: A Systematic Literature Review and Bibliometric Analysis - Syifaurrahmadania Syifaurrahmadania; Kamid Kamid; Syamsir Sainuddin (Journal of General Education and Humanities, 2025)
This study aims to map global research developments on learning trajectories in mathematics education through a systematic literature review and bibliometric analysis. Data were obtained from the Scopus database, with 1,957 initial records screened and 65 relevant articles analyzed based on predefined inclusion and exclusion criteria to ensure relevance and methodological rigor. Bibliometric mapping using VOSviewer was conducted to visualize the evolution of topics, co-authorship networks, methodological trends, and cross-country dissemination. The findings indicate a notable shift from conceptual discussions to classroom-based implementations, the integration of ethnomathematics, and technology-supported instructional designs that promote contextual and student-centered learning. Furthermore, the analysis identifies four dominant research clusters, namely student thinking pathways, curriculum learning progressions, teacher professional development, and digital learning tools. Indonesia appears as the most productive contributor, driven by PMRI traditions and design research practices, alongside a gradual rise in contributions from other countries. This study contributes to the field by highlighting ethnomathematics and technological innovation as emerging research directions and by providing a conceptual roadmap to guide future investigations. The results offer practical implications for educators and researchers in designing culturally responsive learning pathways that deepen mathematical understanding and align with the demands of 21st-century learning.